2020
DOI: 10.1158/1535-7163.mct-19-0189
|View full text |Cite
|
Sign up to set email alerts
|

Selective PRMT5 Inhibitors Suppress Human CD8+ T Cells by Upregulation of p53 and Impairment of the AKT Pathway Similar to the Tumor Metabolite MTA

Abstract: Genetic alterations in tumor cells provide promising targets for antitumor therapy. Recently, loss of methylthioadenosine phosphorylase (MTAP), a deletion frequently occurring in cancer, has been shown to create vulnerability to the inhibition of the protein arginine methyltransferase 5 (PRMT5). MTAP deficiency leads to accumulation of methylthioadenosine (MTA), which reduces PRMT5 activity, and thus, sensitizes the tumor cells to selective PRMT5 inhibitors (PRMT5i). PRMT5i are investigated as a new strategy t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…In other immune cell populations, it has been shown that MTA exerts its suppressive effect by different mechanisms. One supposed mechanism is the interaction with adenosine receptors due to the adenosine residue in MTA and another one due to its intracellular inhibition of the protein arginine methyltransferase 5 (PRMT5) ( 8 , 21 , 22 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In other immune cell populations, it has been shown that MTA exerts its suppressive effect by different mechanisms. One supposed mechanism is the interaction with adenosine receptors due to the adenosine residue in MTA and another one due to its intracellular inhibition of the protein arginine methyltransferase 5 (PRMT5) ( 8 , 21 , 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our group discovered that MTA blocks T cell metabolism and proliferation, thereby suppressing the induction of antigen-specific CD8 T cells and cytokine production by CD4 T cells. Interestingly, the MTA effect was reversible since T cells regained their proliferative capacity after removal of MTA from the culture medium ( 7 , 8 ). Moreover, TNF production in macrophages upon toll-like receptor (TLR) stimulation, e.g., with LPS, is sufficiently suppressed by MTA in an adenosine A2 receptor-dependent manner ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Toxicity was screened in 2 concentrations (10 µM and 100 µM) for 96 h in a final volume of 200 µL. For positive control (representing toxicity), we used a toxic concentration (25 µM) of NSC-57969 [28]; and for negative control, we used 0.4% DMSO-containing medium (referring to 100% growth). Fluorescent intensity of mCherry was detected by Perkin Elmer EnSpire Multimode Plate Reader (fluorescent cells were characterized in our earlier publications) [15,29].…”
Section: Biological Evaluationmentioning
confidence: 99%